High-accuracy EEG-based driver fatigue detection using feature-coupled tensor decomposition for multimodal brain connectivity analysis - Tian Yan; Hechong Su; Zengyao Yang; Aimin Zhang; Yidan Ma; Xiaolong Wang; Yue Wu; Li Yan; Yichen Wang; Jianfu Cao (Cognitive Neurodynamics, 2026)

Mechanisms of lime-induced N2O mitigation in acidic soils: A meta-analysis of microbial activity and substrate dynamics - Kiya Adare Tadesse; Tianfu Han; Zhe Shen; Nano Alemu Daba; Jiwen Li; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Applied Soil Ecology, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Potential Functions of the Gut Microbiome and Modulation Strategies for Improving Aquatic Animal Growth - Zhimin Zhang; Qiushi Yang; Haokun Liu; Junyan Jin; Yunxia Yang; Xiaoming Zhu; Dong Han; Zhigang Zhou; Shouqi Xie (Reviews in Aquaculture, 2025)
The increase in the body weight of animals, a pivotal indicator closely tied to production, is important to the aquaculture industry. Despite remarkable variability in gut microbiomes, which are intricately associated with their hosts and affect overall performance, fitness, and physiological outcomes, across individuals and species, the development and practical application of gut microbiota modulation in aquaculture remain underdeveloped. In this review, we systematically examine the advancements with a focus on the gut microbiomes of aquatic animals with different growth rates by literature search, summarizing the existing knowledge regarding the diversity, composition, and significance of the microbiome in individual growth. The comparative analysis reveals substantial alterations in the gut microbiome that correspond to changes in the growth rate of aquatic animals, with a species bias toward more carnivorous fish, and shrimps and sea cucumbers in nonfish species. The present review also discusses comparative gut microbiome research in aquaculture as an emerging field with great potential for advancing our understanding of animal growth, screening candidate probiotics, and facilitating microbiome modulation strategies. Besides, the present gaps in the knowledge of the gut microbiome associated with the growth and production of farmed animals have been highlighted. We propose potential directions to address emerging challenges and opportunities in this field, such as priority effects on gut microbiome establishment, especially in the early stage, and screening of host‐derived probiotics across various aquatic animals. Finally, we provide a conceptual framework for enhancing animal farming practices in aquaculture through intensified gut microbiome research.

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.

Grazing weakens N-addition effects on soil greenhouse gas emissions in a semi-arid grassland - Zhen Wang; Xiumin Zhang; Mengyuan Wang; Lan Li; An Hu; Xianjiang Chen; Shenghua Chang; Fujiang Hou (Agricultural and Forest Meteorology, 2023)

Effects of temperature fluctuation on the development of cyanobacterial dominance in spring: implication of future climate change - Min Zhang; Baoli Qin; Yang Yu; Zhen Yang; Xiaoli Shi; Fanxiang Kong (Hydrobiologia, 2016)